LENDAWI (THE LANNY TRIBE LAMENTATION): ITS STRUCTURE, TYPES, AND SOCIO-CULTURAL VALUES - Manase Halitopo; Pemius Yikwa; Napius Kogoya (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study centered on the Lendawi (The Lanny Tribe Lamentation): Its Structure, Types, and Socio-Cultural Values. This Lendawi, as part of the Lanny culture, should be carried out by the Lanny community. The objectives are (1) to explain the structure of the Lendawi (Lanny lamentation), (2) to find out the type of stanza among the Lanny tribe, (3) to discuss on what occasions the Lendawi (Lanny lamentation) lamented, and (4) to elaborate the socio-cultural values contained in the Lendawi (Lanny lamentation). This research is qualitative because it only gives explanations about a problem in the form of words, not numbers. The writer found a structural pattern in the lendawi structure. Pattern (1) for men: silent trigger (inhale) + men starting pattern (2) for women: silent trigger (inhale) + women starting. Occasion: (1) to mourn the death of twenty-one people; (2) to welcome the new family who has just returned from a foreign land; (3) to release the family member to go overseas; (4) to release a girl to marry and follow her husband; (5) to remember a family member who has died; (6) to thank people for offering; (7) to mourn for a person who looks similar to a family member (dead or alive); and (8) to think about hard work in the garden that used to be shared with other family members (either dead or alive but living in some other place). Types of stanzas range from 3 lines (triplet) up to 12 lines (sonnet) or more. Sociocultural values are as follows: 1. Kinship address, 2. Using local cultural expressions, e.g., “rainfall,” “white, 3. Mount Tari, 4. The Donggi and Konda rivers 5. The Walem bird 6. The Gweage River, 9. The Ugwa River, 12. The Prikokir Bird 13. Special respect for uncles (mother’s brothers), 14. The Mukoko Clan, and 15. Grandmother as a protector for orphans.